PERBEDAAN KARAKTERISTIK LESI PADA FOTO THORAX PASIEN TB PARU DISERTAI DIABETES MELITUS DENGAN PASIEN TB PARU TANPA DISERTAI DIABETES MELITUSSEBUAH SYSTEMATIC REVIEW - Abdillah Khoirul Fat-hi (2021)
Indonesia is in the 3rd rank as a country with Tuberculosis (TB) in the world. The high number is inseparable from the existence of risk factors that influence, one of which is Diabetes Mellitus (DM). High blood sugar levels in DM patients can help bacterial growth and worsen TB patients condition. This Association can be seen based on the differences in the characteristics of the lesions of TB patients without DM and TB patients with DM through chest X-ray images. This study aims to determine the differences in lesion characteristics on the chest photo image of pulmonary TB patients accompanied by DM with TB patients without DM by collecting various related literature. Method: Systematic Literature Review by conducting journal searches using the Google Scholar search portal, PubMed, and Science Direct. Journals that discuss DM, TB, chest photos, and characteristics of lesions. Results: Eight studies were explaining the differences in the characteristics of lesions based on chest radiographs, namely moderate lesion area in TB patients with DM and minimal lesion area in TB patients without DM, the presence of cavities, and the number of cavities in TB patients with DM was higher than TB patients without DM. , however, there was no difference in location between the two. Conclusion: There are differences in the characteristics of the lesions on the chest X-ray from a broader type of lesion, more frequent cavities, and a higher number of cavities in TB patients with DM. Keywords: Tuberculosis, Diabetes Mellitus, Chest X-ray, Characteristics of a Lesion